1998
DOI: 10.3133/ofr98754
|View full text |Cite
|
Sign up to set email alerts
|

Phanerozoic tectonic evolution of the circum-north Pacific

Abstract: The Phanerozoic tectonic evolution of the Circum-North Pacific is recorded mainly in the erogenic collages of the Circum-North Pacific mountain belts that separate the North Pacific from the eastern North Asian and western North American Cratons. The collages consist of tectonostratigraphic terranes, composed of fragments of igneous arcs, accretionary-wedge and subduction-zone complexes, passive continental margins, and cratons, that are overlapped by continental margin arc and sedimentary basin assemblages. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(181 citation statements)
references
References 57 publications
(176 reference statements)
2
169
1
9
Order By: Relevance
“…There is an alternative and less popular proposal suggesting that Siberia has a good match with the western US, based on the comparison of Mesoproterozoic lithologies (Sears and Price, 2000). From my point of view, Siberia cannot be placed to the north of Laurentia, because of the Hyperborean craton in the Russian Northeast and Alaska (Nokleberg et al, 1998), largely ignored in most published reconstructions. Its presence does not allow a proper match of Siberian Archaean terranes with their equivalents in Laurentia.…”
Section: Reassembling the Supercontinent Columbiamentioning
confidence: 94%
“…There is an alternative and less popular proposal suggesting that Siberia has a good match with the western US, based on the comparison of Mesoproterozoic lithologies (Sears and Price, 2000). From my point of view, Siberia cannot be placed to the north of Laurentia, because of the Hyperborean craton in the Russian Northeast and Alaska (Nokleberg et al, 1998), largely ignored in most published reconstructions. Its presence does not allow a proper match of Siberian Archaean terranes with their equivalents in Laurentia.…”
Section: Reassembling the Supercontinent Columbiamentioning
confidence: 94%
“…In the Early Cretaceous, although the main portion of the MongolOkhotsk Ocean had closed, a remnant ocean still remained to the north of the Mohe Basin (Zonenshain et al, 1990;Nokleberg et al, 2000;Parfenov et al, 2010) (Fig. 11C).…”
Section: Escape Tectonics In East Asia During the Early Cretaceousmentioning
confidence: 95%
“…A number of Lower Cretaceous basaltic rocks have been found along the fault (Hankard et al, 2007;Van Hinsbergen et al, 2008), suggesting that it was active during the Early Cretaceous. Geological and paleomagnetic data have suggested that the Mongol-Okhotsk suture zone underwent sinistral transpressional faulting during the Early Cretaceous (Halim et al, 1998;Nokleberg et al, 2000;Parfenov et al, 2010). A sinistral strike-slip ductile shear zone parallel to the Mongol-Okhotsk suture formed in the western part of the Mohe Basin (J.Y.…”
Section: Escape Tectonics In East Asia During the Early Cretaceousmentioning
confidence: 98%
See 1 more Smart Citation
“…Vinogradov, 1995) that form 30 to 45 km thick crust (Bogdanov and Khain, 2000). In the NW Pacific and Kamchatka, nearly orthogonal subduction, dipping at ϳ45°angle of the Cretaceous Pacific plate for the past 43 Ma (e.g., Engebretson et al, 1985;Nokleberg et al, 1998) has enriched the mantle wedge with volatiles and, as is discussed in the text, has caused a regionally extensive high ␦ 18 O source. Accreted oceanic arcs have added high-␦ 18 O mafic and silicic rocks (Fig.…”
Section: Radiogenic Isotope Studiesmentioning
confidence: 97%